The possible use of pilotless aircrafts for operative monitoring of soil productivity - I. Yu. Savin; Yu. I. Vernyuk; I. Faraslis (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
As seen from a comprehensive review of literature sources, at the current stage of technological development and simplicity the pilotless aircrafts should be considered as a reliable tool for operative monitoring of soils and crops on fields and areas of small farms. The possibilities to use the imagery obtained by pilotless aircrafts are predetermined by a type of survey apparatus to a considerable extent. At present, the miniature survey apparatus permits to obtain images, the spectral resolution of which can be compatible with those obtained by satellites. Today, the images of pilotless aircrafts are used to give a visual assessment of any object to be surveyed. There are publications devoted to the computer analysis of images including those used for agricultural purposes. The experience is becoming common to use the imagery obtained by pilotless aircrafts and their computer analysis for constructing digital models of the field relief, monitoring over the soil erodibility and operative valuation of the agricultural crops state. Being compared with satellite imagery, the data of pilotless aircrafts have a number of advantages in aerial surveying. The major limits to use data obtained by pilotless aircrafts consist in insufficient miniaturization of the surveying apparatus and the fact that the monitoring cannot be organized to control over large areas.